A Zn(ii) complex with large channels based on 3′-nitro-biphenyl-3, 5, 4′-tricarboxylic acid: synthesis, crystal structure, fluorescence sensing of ATP, ADP, GTP, and UTP in aqueous solution and drug delivery. Issue 44 (30th October 2017) - Zhang, De-chun; Li, Xia
Abstract : A 3D Zn(ii )–MOF with large cubic channels was synthesized. It showed fluorescence sensing of ATP, ADP, GTP, and UTP. Furthermore, it exhibited a remarkable capacity for and controlled release of 5-fluorouracil. Abstract : A new coordination complex, namely, [Zn7 L2 (HL)2 (OH − )4 (H2 O)2 ]·2H2 O (1 ) [H3 L = 3′-nitro-biphenyl-3, 5, 4′-tricarboxylic acid] was synthesized by a solvothermal reaction. Complex1 has a 3D open framework with heptanuclear cluster [Zn7 O2 (OH)4 ] secondary building units (SBUs) and features an unexpected large porous structure with a pore size of 16.5 × 19.5 Å 2, which shows 37.0% porosity as calculated by PLATON. Adenosine triphosphate disodium salt (ATP), adenosine-5′-diphosphate disodium salt (ADP), guanosine 5′-triphosphate (GTP), or uridine 5′-triphosphate (UTP) was discriminated from other phosphate anions using fluorescence spectral analysis by adjusting the excitation wavelength at 287, 287, 306, or 337 nm. Complex1 showed fluorescence sensing of ATP, ADP, GTP, and UTP in aqueous solution. In addition, complex1 also exhibited a remarkable capacity for the anticancer drug 5-fluorouracil (5-FU), with a loading content of 46.5 wt%, and presented a slow controlled drug release.